ANALYSIS OF LEGAL REVIEW OF MEDICAL INFORMATION RELEASE TO ENSURE THE CONFIDENTIALITY OF PATIENT IDENTITY - Marwiyah (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
Assessment of health service can be viewed from the recording on the file of medical record, which can provide information about the patient's social identity, diagnosis of disease, disease history, examination and treatment which must be kept confidential by doctors, nurses, health workers and manager of the healthcare facility. This study aimed to describe legal review of the medical information release in ensuring patient confidentiality. The research used normative-juridical approach through literature study which examines secondary data in the form of primary and secondary legal materials. The results of the study showed that health care facilities are responsible for protecting health information contained in medical records against possible loss, damage, falsification and unauthorized access. Maintaining information security, accuracy of information and ease of access to information are demanded to health service organizations and health practitioners as well as authorized third parties. Meanwhile, parties who need information must always respect patient privacy. Healthcare facilities are obliged to maintain the confidentiality of the information contained in the medical record and are not allowed to release it to irresponsible people/institutions. Requests for medical information must go through the established procedures to protect patient privacy and avoid lawsuits.